2021
DOI: 10.1186/s40249-020-00791-3
|View full text |Cite
|
Sign up to set email alerts
|

Neglected tropical diseases activities in Africa in the COVID-19 era: the need for a “hybrid” approach in COVID-endemic times

Abstract: With the coronavirus disease 2019 (COVID-19) pandemic showing no signs of abating, resuming neglected tropical disease (NTD) activities, particularly mass drug administration (MDA), is vital. Failure to resume activities will not only enhance the risk of NTD transmission, but will fail to leverage behaviour change messaging on the importance of hand and face washing and improved sanitation—a common strategy for several NTDs that also reduces the risk of COVID-19 spread. This so-called “hybrid approach” will de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 14 publications
0
31
0
2
Order By: Relevance
“…Research conducted in low and middle-income countries (LMICs) where there is high prevalence of cooking with wood and other polluting fuels demonstrates that elevated PM 2.5 levels found in household air pollution places the population at increased risk for infectious, cardiovascular and respiratory diseases and mortality ( Apte et al, 2015 ). As Chile had some of the highest rates of COVID-19 cases globally during April-August 2020 ( Undurraga et al, 2021 ), it is possible that increased PM 2.5 levels in Temuco may have exacerbated COVID-19 transmission ( Fattorini and Regoli, 2020 ; Zhu et al, 2020 ). Older individuals (≥65 years), who have the greatest health risk from exposure to wood smoke ( Díaz-Robles et al, 2015 ), and are more likely to suffer from severe symptoms of COVID-19, can be particularly vulnerable ( Undurraga et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted in low and middle-income countries (LMICs) where there is high prevalence of cooking with wood and other polluting fuels demonstrates that elevated PM 2.5 levels found in household air pollution places the population at increased risk for infectious, cardiovascular and respiratory diseases and mortality ( Apte et al, 2015 ). As Chile had some of the highest rates of COVID-19 cases globally during April-August 2020 ( Undurraga et al, 2021 ), it is possible that increased PM 2.5 levels in Temuco may have exacerbated COVID-19 transmission ( Fattorini and Regoli, 2020 ; Zhu et al, 2020 ). Older individuals (≥65 years), who have the greatest health risk from exposure to wood smoke ( Díaz-Robles et al, 2015 ), and are more likely to suffer from severe symptoms of COVID-19, can be particularly vulnerable ( Undurraga et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Holden et al recommended that a two-year course is possibly realistic to bring desirable research outcomes [ 13 ]. Feng et al reported on an 18-month follow-up to post-training initiatives where 11 of 12 participants generated manuscripts published by peer-review international journals [ 45 ]. Further strategies targeted at linking research policy and practice may increase the success of RCB aimed at enhancing EBP and emphasizing that evidence must come at least in part from research conducted within the given setting [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…and Ircinia sp. Terpene Furospinulosin-1 14.2 μg mL −1 [ 73 ] Furospongin-1 4.8 μg mL −1 Heptaprenyl- p -quinol 18.9 μg mL −1 Tedania braziliensis Alkaloid Pseudoceratidine NA [ 75 ] Dysidea avara Quinone Sesquiterpene avarone and avarol L. infantum amastigote (7.64 and 3.19 μmol/L) and promastigotes (28.1 and 7.42 μmol/L), and L. tropica promastigotes (20.28 and 7.08 μmol/L) [ 76 , 77 ] Marine Bacteria Paenibacillus polymyxa Alkaloid Paenidigyamycin A L. major (0.75 μmol/L) and L. donovani (7.02 μmol/L) [ 78 ] Streptomyces sanyensis Alkaloid Indolocarbazole staurosporine L. amazonensis promastigotes and amastigote (0.06–10.65 μmol/L), L. donovani promastigotes (0.50 – > 40 μmol/L) [ 79 ] Streptomyces sp. strain 11 (GU214750) Alkaloid Indolocarbazole staurosporin L. major promastigotes with EC50 5.30 μM [ 67 ] Streptomyces sp.…”
Section: Marine Actinomycetes As Sources For Antileishmanial Drugsmentioning
confidence: 99%
“… Polyketide Coibacin A –D 0.68–4.99 μg mL −1 [ 87 ] Marine Algae Bifurcaria bifurcate (Brown alga) Terpene Bifurcatriol L. donovani amastigotes (18.8 μg/ml) [ 88 ] Dictyota spirali Terpene Spiralyde A L. amazonensis promastigotes (15.47 ± 0.26 and 36.81 ± 5.20 μmol/L) [ 89 ] Cystoseira baccata Terpene tetraprenyltoluquinol and tetraprenyl L. infantum promastigotes and amastigotes (44.9 ± 4.3 and 94.4 ± 10.1 μmol/L) [ 90 ] Stypopodium zonale Terpene Atomaric acid and its methyl ester derivative L. amazonensis intracellular amastigotes (20.2 and 22.9 μmol/L) [ 91 ] Laurencia viridis (red algae) Terpene Oxasqualenoid metabolites Promastigotes of L. Amazonensis and L. donovani (5.40–46.45 μmol/L) [ 92 ] Marine Fungi Eurotium repens Polyketide Tetrahydroauroglaucin 22 μg mL −1 [ 93 ] Flavoglaucin 23 μg mL −1 Auroglaucin 7.5 μg mL −1 Paecilomyces sp. 7A22 Lactone Harzialactone A L. amazonensis promastigotes forms (5.25 μg/ml) and intracellular amastigotes (18.18 μg/ml) [ 77 , 94 ] Marine seaweed …”
Section: Marine Actinomycetes As Sources For Antileishmanial Drugsmentioning
confidence: 99%